Intra-cyclic distance per stroke phase, velocity fluctuations and acceleration time ratio of a breaststroker's hip: A comparison between elite and nonelite swimmers at different race paces - Leblanc, H.; Seifert, L.; Tourny-Chollet, C.; Chollet, D. (International Journal of Sports Medicine, 2007)
The aim of this study was to compare the intra-cyclic velocity graphs of breaststroke swimmers at two skill levels in relation to their movement phases. Two groups of nine male swimmers were videotaped underwater at three swimming race paces corresponding to their actual competitive times for the 200-m, 100-m and 50-m breaststroke. Their forward intra-cyclic hip velocity was recorded with a velocity-meter. The breaststroke cycle was divided into four phases: leg propulsion, leg-arm lag phase, arm propulsion, and arm and leg recovery. From the velocity-time data, the following parameters were computed: an index of velocity fluctuations (IVF), the distance covered during each stroke phase, and an acceleration-deceleration time ratio (ADTR). The main results showed that in both groups of swimmers, when the race pace increased, the distance covered during the leg-arm lag phase decreased, while the other swimming phases remained stable. When expressed in relative values, the percentage of distance covered during the leg-arm lag phase decreased. In nonelite swimmers, the percentage of distance covered in the other stroke phases increased significantly, while only a tendency was noted in the elite group. Elite swimmers demonstrated a higher ADTR at the 50-m pace than at their 100-m and 200-m paces. An inter-group comparison showed that elite swimmers had higher values for the IVF and ADTR, which indicated their capacity to accelerate to boost the swim and highlighted the relevancy of these factors to discriminate skill level.